Clinical relevance of hepatitis G virus (HGV) infection in heart transplant patients - Kallinowski, Birgit; Janicki, Manuela; Seelig, Renate; Seipp, Stefanie; Oswald, Jens; Dengler, Thomas; Schnitzler, Paul; Theilmann, Lorenz; Stremmel, Wolfgang (The journal of heart and lung transplantation, 1999)
To investigate whether the recently discovered hepatitis G virus (HGV) influences the clinical outcome of heart transplant recipients under immunosuppression, we determined the prevalence of HGV infections correlated with liver function and survival in 51 patients. Presence of HGV RNA and anti-E2, a marker for resolved HGV infection, were serially tested in sera from patients before and after heart transplantation (HTX) by nested RT-PCR and ELISA. Four of 51 (7.8%) patients before transplantation, and 22 of 50 patients (44%) after transplantation showed signs of persistent or resolved HGV infection. HGV infection was not associated with impairment of liver function or with patient survival. In summary, presence of HGV infection does not influence the clinical outcome in heart transplant patients.
Available online 5 August 1999
Gesehen am 07.04.2021